2015
DOI: 10.1039/c4ta06861k
|View full text |Cite
|
Sign up to set email alerts
|

A novel structure for enhancing the sensitivity of gas sensors – α-Fe2O3 nanoropes containing a large amount of grain boundaries and their excellent ethanol sensing performance

Abstract: Novel one-dimensional (1D) a-Fe 2 O 3 nanostructures containing a large amount of grain boundaries have been synthesized through the combination of electrospinning and precursor-calcination techniques. The as-prepared a-Fe 2 O 3 nanostructures were composed of orderly arranged building blocks (a-Fe 2 O 3 nanoparticles) which are connected to each other. The investigation of the morphology evolution revealed that the template fiber geometry has an influential impact on the grain growth behavior during preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…PL studies have confirmed the absence of additional defect states in aluminium doped samples, thus ruling out contribution from material defects in volume charge mobilization at the sensor operational temperature (see the ESI †). 46 According to the grain boundary model, [47][48][49][50] chemisorption on metal oxide surface leads to change in grain boundary thickness, affecting electron transport. From the room temperature capacitive studies, it has been observed that for all the samples, decrease in capacitance on exposure to ethanol gas is negligible (see the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…PL studies have confirmed the absence of additional defect states in aluminium doped samples, thus ruling out contribution from material defects in volume charge mobilization at the sensor operational temperature (see the ESI †). 46 According to the grain boundary model, [47][48][49][50] chemisorption on metal oxide surface leads to change in grain boundary thickness, affecting electron transport. From the room temperature capacitive studies, it has been observed that for all the samples, decrease in capacitance on exposure to ethanol gas is negligible (see the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a need to develop high-performance gas sensors with high sensitivity, low operating temperature and good stability for real-time monitoring of toluene and xylene. A variety of metal oxide semiconductors have been used as sensing materials to detect VOCs, such as ZnO, [4][5][6] SnO2, [7][8][9] In2O3, [10][11][12] Co3O4, [13][14][15] TiO2, 16,17 WO3, [18][19][20][21] Fe2O3, [22][23][24] Cu2O/CuO, 25,26 and NiO. 27 Among these metal oxide semiconductors, Co3O4 is believed to be a promising candidate for sensing of toluene and xylene because of its excellent catalytic activity for oxidizing them at low temperature which results from its larger adsorption amount of oxygen 28 on the surface than others and multivalent properties facilitating redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, cyclic measurements (inset) for linear regression showed a stable baseline (R 0 ) through the test. Thus, α-Fe 2 O 3 /Ag 3.0 wt% have demonstrated appropriate features for ethanol vapor sensing such as other hematite-based sensors [ 23 , 35 , 36 , 37 , 38 ]. Higher sensibility at 25 °C, short-time gas response, rapid recovery, and excellent repeatability (ΔR/R o ), even at low concentrations (2 mg L −1 ), is the greater contribution of this work.…”
Section: Resultsmentioning
confidence: 99%
“…Sensors of n-type Fe 2 O 3 nanobelts assembled by Fan et al showed a 2.2 gas response when exposed to 50 mg L −1 of ethanol at 285 °C [ 36 ]. Yan et al prepared α-Fe 2 O 3 nanoropes (specific surface area: 18.95 m 2 g −1 ) sensing 100 mg L −1 of ethanol with 10.2 of relative signal at 240 °C [ 37 ]. The materials described above operate in the range of 250–300 °C to reach optimal response towards ethanol.…”
Section: Introductionmentioning
confidence: 99%